Endocardial left ventricular pacing for cardiac resynchronization: systematic review and meta-analysis. Issue 1 (10th January 2017) - Gamble, James Hugo Phillimore; Herring, Neil; Ginks, Matthew; Rajappan, Kim; Bashir, Yaver; Betts, Timothy Rider
Abstract: Aims: Endocardial left ventricular (LV) pacing for Cardiac Resynchronization Therapy has been proposed as an alternative to conventional LV lead placement via the coronary sinus. In order to assess the relative benefits and risks of this technique, we have performed a meta-analysis of published reports. Methods and results: A systemic search was performed using online databases to identify studies of lead-based endocardial pacing. A random-effects meta-analysis was performed, to assess the rate of complications and clinical response (defined as ≥1 decrease in NYHA class). We selected 23 studies, including 384 patients. The trans-atrial septal technique was used in 20 studies, 1 used the trans-ventricular apical technique, and 2 used the trans-ventricular septal technique. Mean age was 66 years, male 66%, EF 26%, NYHA class 3.0. Procedural success rates were over 95% in all studies. Clinical response was reported by 16 studies for 262 patients, giving a response estimate of 82% (95% CI 71–89%). There was significant heterogeneity, and response in the only large study was 59%. Thromboembolic (TE) complications were reported by all studies, over 22 ±32 months follow up. The rate of stroke was 2.5 events per 100 patient years (95% CI 1.5–4.3), and TIA 2.6 (1.1–6.1). The mortality rate was 4.5 (1.5–13.6) per 100 patient years. Conclusion: LV endocardial pacing appears to be a viable technique when conventional lead placement is not possible. Response rates were heterogeneous but comparable with conventional CRT. There is likely to be a small increase over expected rates of stroke, although included patients were high risk.